Pengembangan Media Pembelajaran Komik Bermuatan Karakter Gemar Membaca untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas IV Sekolah Dasar - Mutiara, Mutiara; Dadan Setiawan; Idah Faridah Laily (Journal of Humanities, Social Sciences, and Education, 2025)
This study was motivated by the low reading comprehension skills of fourth-grade elementary school students, which has become a major concern in the field of education. The purpose of this research is to develop comic-based learning media that incorporates the character of reading enthusiasm to improve student’s reading comprehension skills. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Developmet, Implementation, and Evaluation. The results of expert validation indicated that the media is appropriate for use, and student responses showed a high level of interest in the media. The Wilcoxon test yieled a significance value of 0,000 indicating a meaningful difference between the pre-test and post-test results. The N-Gain test showed an improvement of 76,69% in the limited trial and 80,62% in the wide-scale trial, both categorized as effective. Therefore, comic media that incorporates the character of reading enthusiasm is effective in enhancing students’ reading comprehension skills.